(3efgL eYGUQs - (3NGdO eMeO WdGd(B, (3Hfj MeOGfs; (3GOQjS hGFd eMeO(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ h GdJhRjY(B,s, 2009)
(3jJfGhd gPG GdcJGH gjcd YedjI GdJNWjW GdGSJQGJjLj eSJhjGJ GdJNWjW hGdeTGQchf aj YedjI GdJNWjW GdJdjd GdHjFj GdOGNdj MjK YQVJ aUhdg cGdJGdj GdaUd GdChd (B: (3eGgjI GdJNWjW GdGSJQGJjLj (B: (3eaghe GdJNWjW GdGSJQGJjLj hJWhQg (B: (3GdJNWjW GdGSJQGJjLj (B: (3GdNUGFU (B.. (3GdCgejI hGdahGFO (B: (3eOGQS GdacQ GdJNWjWj (B: (3adSaGJ GdJNWjW GdGSJQGJjLj(B-(3GdaUd GdKGfj (B: (3YedjI GdJNWjW GdGSJQGJjLj (B: (3gjcd YedjI GdJNWjW GdGSJQGJjLj (B: (3NWhGJ YedjI GdJNWjW GdGSJQGJjLj (B: (3eSJhjGJ GdJNWjW hGdeTGQchf aj YedjI GdJNWjW(B-(3GdaUd GdKGdK (B: (3GdJMdjd hGdJTNjU GdHjFj (B: (3eaghe GdHjFI hGdJMdjd GdGSJQGJjLj ddHjFI (B: (3GdJMdjd GdHjFj GdOGNdj (B: (3CSGdjH hJbfjGJ GdJMdjd GdHjFj GdOGNdj(B-(3GdaUd GdQGHY (B: (3JMOjO hJYQja GdGJLGg GdGSJQGJjLj (B: (3GdQDjI GdeSJbHdjI defXeGJ GdCYeGd (B: (3HjGf GdQSGdI defXeGJ GdCYeGd (B: (3GdefXheI GdbjejI defXeGJ GdCYeGd (B: (3GdZGjGJ hGdCgOGa GdGSJQGJjLjI ddefXeGJ (B: (3GdeMGhQ GdGSJQGJjLjI GdQFjSI(B-(3GdaUd GdNGeS (B: (3UjGZI hEYOGO GdNWI GdGSJQGJjLjI (B: (3eGgjI GdGSJQGJjLjI (B: (3UjGZI GdNWI GdGSJQGJjLjI (B: (3bhi GdJhLjg GdGSJQGJjLj(B-(3GdaUd GdSGOS (B: (3GdHOGFd hGdNjGQGJ GdGSJQGJjLjI (B: (3eGgjI GdHOGFd hGdNjGQGJ GdGSJQGJjLjI (B: (3JJUfja GdHOGFd GdGSJQGJjLjI(B-(3GdaUd GdSGHY (B: (3fTQ hJfajP GdNWI GdGSJQGJjLjI (B: (3fTQ hEjUGd GdNWI GdGSJQGJjLjI (B: (3JfajP GdNWI GdGSJQGJjLjI(B-(3GdaUd GdKGef (B: (3GdNWI GdJTZjdjI (B... (3JMOjO eHGOQGJ hHQGeL GdYed (B: (3GdNWI GdJTZjdjI(B-(3GdaUd GdJGSY (B: (3GdQbGHI hJbjje fJGFL GdCOGA GdGSJQGJjLj (B: (3eGgjI GdJbjje hGdQbGHI GdGSJQGJjLjI (B: (3GdCOGA hhSGFd bjGS GdCOGAs
(3HjHdjhZQGajG fgGjI cd aUd s
Keywords: (3GOGQI CYeGds; (3GSJQGJjLjIs; (3JNWjWs